Combating illegal migration by means of criminal law - Mytrofanov, Ihor (Migration & Law, 2023)
The article analyzes the legal wording of Article 332 of the Criminal Code of Ukraine «to promote the organization smuggle across the state border with advice, guidance ...». When this is taken into account and the etymological aspect and general provisions of complicity in the crime. It is stated that under the phrase literally be understood an active part in the implementation of complex measures for the transport of persons or transferred across the state border. But can we implement a set of measures to help with advice or instructions? It argued the need to clarify the wording of Article 332 of the Criminal Code of Ukraine. Article 332 of the Criminal Code of Ukraine «Organization of illegal migration» should read as follows: «1. Organization of illegal entry into Ukraine, stay on the territory of Ukraine, transit passage (transit) through the territory of Ukraine or departure from Ukraine of a foreigner (person without citizenship) or creation of conditions for this, committed for selfish motives (organization of illegal migration), — is punishable by arrest, restriction of liberty for a term of three to five years or deprivation of liberty for the same term with confiscation of vehicles or other means of committing a criminal offense. 2. The organization of illegal migration, committed in a manner dangerous to the life or health of a foreigner (a stateless person), or combined with cruel or degrading treatment, or committed re peatedly, or by a group of persons with a prior conspiracy, or an official using his official powers, — shall be punished by deprivation of liberty for a term of five to seven years with confiscation of vehicles or other means of committing a criminal offense and with or without confiscation of property».